Controller placement optimization in hierarchical distributed software defined vehicular networks - Ma, Maode (2019)
Recently, a new paradigm has emerged, named as Software Defined Vehicular Network (SDVN) which applies the concept of Software Defined Networking (SDN) in Vehicular Ad-hoc Network (VANET), to overcome the shortcomings in vehicular networks. With the introduction of SDN, VANET has been provided with flexibility and programmability along with a performance improvement. However, the improvement comes at a cost of higher operational delay because, the controllers are placed far away from the data plane in the existing SDVN architectures. As an alternative, we have previously proposed to bring the control plane down to Road Side Unit (RSU). In this study, we further extend this work and introduce a hierarchical distributed controller architecture where the top tier of controllers are regionally distributed on the Internet and the bottom tier of controllers are placed in several selected RSUs closer to the vehicles so that the latency induced by the system becomes low. We further present a novel controller placement model for the RSU level controllers based on the p-median facility location problem with the delay and the significance of the RSU location as the factors to achieve the optimization heuristically as an integer quadratic programming problem. With the help of the simulation results, we show that our proposed controller placement model can optimize the placements of controllers with a lower latency compared to other possible controller placement methods including the existing SDVN architectures and conventional VANETs.